Severe mammary fibroepithelial hyperplasia due to single injection of medroxyprogesterone acetate in two male cats - Voorwald, Fabiana Azevedo; Lopes, Carlize; Silveira, Gabriel Coutinho; Lima, Daniela Tavares; da Silva, Maria de Fátima Cotta; Andreão, Natália Brioschi; Toniollo, Gilson Hélio [UNESP] (FapUNIFESP (SciELO), 2021)
Thirty and forty days after a 50 mg medroxyprogesterone acetate injection, respectively, two mixed-breed, 7 and 8-month-old entire male cats presented diffuse enlargement of thoracic and abdominal mammary glands, with ulceration, abscessation and necrosis. One patient was treated with 10 mg/kg aglepristone, antibiotic therapy, analgesic and non-steroidal anti-inflammatory compound; however a worse enlargement of mammary glands, necrosis and clinical condition was noted two days after antiprogestin injection. The second patient was submitted to surgical procedure without previous medical treatment. A partial bilateral mastectomy and conventional orchiectomy were performed, and both patients presented no clinical abnormalities 10 days after surgical treatment. In the male cat, the interruption of progesterone associated mammary fibroepithelial hyperplasia cannot be based in gonadectomy, being antiprogestin treatment the primary approach. Mastectomy can be a treatment option in selected cases, such as the two cases presented here, in case of antiprogestin treatment failure or in case of extensive ulceration, necrosis and risk of sepsis.
Hiperplasia fibroadenomatosa mamária felina secundária à aplicação única de acetato de medroxiprogesterona em dois felinos machos
Keywords: Aglepristone; Antiprogestin; Exogenous progesterone; Intact male cat